Development and Validation of a Questionnaire to Measure a Medical Student's Interest in the Subject of Community Medicine. - Ali, Syed I.; Begum, Jarina; Kumar, Abhishek; Shikha, Swati; Patil, Sachin K.; Sinha, Ratnesh (Indian Journal of Community Medicine)
Background: Lack of interest has been cited by many studies as the predominant cause for students undervaluing the subject of Community Medicine. However, there are few valid and reliable tools that could measure this interest. To develop and validate a questionnaire to measure a medical student's interest in the subject of Community Medicine. Material and Methods: Cross-sectional study conducted at MTMC Jamshedpur. The Community Medicine Interest Questionnaire (CMIQ) was developed in two phases: item generation and item reduction. Items were generated through a review of the literature, focused group discussions, and in-depth interviews. In the item reduction phase, the content and construct validity of the questionnaire were ascertained. Content validity was carried out by a group of experts based on three parameters: the interrater agreement on the representativeness of the item, the interrater agreement on the clarity of the items, and the content validity index. The construct validity was ascertained through pilot testing of 480 responses from undergraduate medical students. Exploratory factor analysis through principal axis factoring and Promax rotation. Results: Twenty-five items were generated. Three of these items were removed following expert validation. Furthermore, three items were removed after pilot testing. The resulting CMIQ consisted of 19 items distributed over three dimensions: feeling, value, and predisposition to reengage toward the subject. The internal consistency of each of the subscales was ascertained. Conclusions: CMIQ is a valid and reliable tool that can be used to measure such interest for providing educational interventions.